The principles and practice of auditing - Williams, R.Glynne; Mendes, B. (Great Britain : Donnington Press, 1974)
This book examines the principles and auditing for examination and practical purposes.
Includes bibliographical references and index.
MF23/01/2019
Loans
Keywords: Auditing